SUPER ENKRIPSI KRIPTOGRAFI PENGAMAN FILE CITRA MENGGUNAKAN ALGORITMA BEAUFORT CIPHER, VIGENERE CIPHER DAN RIVEST SHAMIR ADLEMAN (RSA) - Fauzi, Achmad (STMIK KAPUTAMA, 2025)
Protection of digital data, particularly image files, has become increasingly vital in today’s rapidly evolving digital landscape. This study focuses on assessing the effectiveness of a combined cryptographic approach involving three algorithms Beaufort Cipher, Vigenère Cipher, and RSA in maintaining the confidentiality and integrity of image files. The Beaufort Cipher, a symmetric encryption algorithm, offers speed and simplicity in the encryption process, while the Vigenère Cipher enhances complexity through the use of extended keys. Meanwhile, RSA, an asymmetric encryption technique, provides an additional layer of security by implementing a public and private key system. Based on a series of experiments, this analysis reveals that a super-encryption method involving all three algorithms produces robust and reliable encryption. Furthermore, the findings provide insight into the strengths and limitations of each algorithm, offering valuable guidance for the future development of more secure data protection systems